2013
DOI: 10.1371/journal.pone.0068007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Serotonin and Dopamine Metabolites in Human Brain Microdialysis and Cerebrospinal Fluid Samples by UPLC-MS/MS: Discovery of Intact Glucuronide and Sulfate Conjugates

Abstract: An UPLC-MS/MS method was developed for the determination of serotonin (5-HT), dopamine (DA), their phase I metabolites 5-HIAA, DOPAC and HVA, and their sulfate and glucuronide conjugates in human brain microdialysis samples obtained from two patients with acute brain injuries, ventricular cerebrospinal fluid (CSF) samples obtained from four patients with obstructive hydrocephalus, and a lumbar CSF sample pooled mainly from patients undergoing spinal anesthesia in preparation for orthopedic surgery. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 50 publications
2
47
1
Order By: Relevance
“…Glucuronic acid conjugates of neurotransmitters, such as serotonin (5-HT) and dopamine (DA), were detected in cerebrospinal fluid (CSF) and microdialysis samples of humans and rats [36–38]. Glucuronic acid conjugates of steroids were also detected in the mouse brain extract [39].…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronic acid conjugates of neurotransmitters, such as serotonin (5-HT) and dopamine (DA), were detected in cerebrospinal fluid (CSF) and microdialysis samples of humans and rats [36–38]. Glucuronic acid conjugates of steroids were also detected in the mouse brain extract [39].…”
Section: Discussionmentioning
confidence: 99%
“…37) Moreover, it has been reported that the glucuronide of the monoamine neurotransmitters, dopamine and serotonin, had been observed in human and rat brains. [38][39][40] Maintaining the proper concentration of a substance in a target site (specific brain region or neurons) is important to perform an effective and safe drug therapy or to maintain homeostasis. The changes in UGT expression in the target site could affect pharmacological and physiological functions owing to the alteration in the concentration of the drugs and neurotransmitters in the brain.…”
Section: )mentioning
confidence: 99%
“…Recent work reveals that sulfoconjugates predominate among serotonin metabolites in fluids extracted from brain cortices of living humans and are major metabolites in brain-ventricle and spinal fluids (61). Studies using subsections of rat brain reveal that MAO inhibition routes dopamine metabolism substantially through the sulfonation pathway and demonstrate the interactivity of the MAO and SULT systems (62,63).…”
Section: Discussionmentioning
confidence: 99%